Evaluation of the Relationship between Aromatase/Sirtuin1 Interaction and miRNA Expression in Human Neuroblastoma Cells - Kartal, Yasemin; Tokat, Unal Metin; Kelicen-Ugur, Pelin; Yılmaz, Serkan; Karahan, Sevilay; Budak, Murat T. (Current Molecular Pharmacology, 2023)
Background: Changes in activation/inhibition of Sirtuin-1 (SIRT1) and aromatase play an important role in a plethora of diseases. MicroRNAs (miRNAs) modulate multiple molecular pathways and affect a substantial number of physiological and pathological processes. Objective: The aim of this study was to investigate any possible interaction between aromatase and SIRT1 in SH-SY5Y cells and to see how there is a connection between this interaction and miRNA expression, if there is an interaction. Methods: In this study, cells were incubated in serum-deprived media for 6, 12, and 24 h. Aromatase and SIRT1 expressions were evaluated by Western blot. The IC50 concentration of SIRT1 activator (SRT1720), SIRT1 inhibitor (EX527), and aromatase inhibitors (letrozole and fadrozole) was determined by the XTT method. Then, CYP19A1 and SIRT1 levels were evaluated in the presence of SIRT1 siRNA or IC50 values for each activator/inhibitor. Finally, CYP19A1, SIRT1 expression and miRNA target gene were assessed with bioinformatic approaches. Results: Aromatase and SIRT1 protein levels were significantly elevated in the cells incubated at 24 h in serum-deprived media (p ≤ 0.05). SIRT1 also positively regulated CYP19A1 in SH-SY5Y cells in media with/without FBS. Serum deprivation depending on time course caused changes in the oxidant/ antioxidant system. While oxidative stress index tended to decrease in the absence of FBS at 24 h compared to the control, it showed a significant decrease at 48 h in a serum-deprived manner (p ≤ 0.001). As a result of bioinformatics analysis, we determined 3 miRNAs that could potentially regulate SIRT1 and CYP19A1. hsa-miR-27a-3p and hsa-miR-181a-5p correlated in terms of their expressions at 24 h compared to 12 h, and there was a significant decrease in the expression of these miRNAs. On the contrary, the expression of hsa-miR-30c-5p significantly increased at 24 h compared to 12 h. Conclusion: Considering the results, a direct link between aromatase and SIRT1 was observed in human neuroblastoma cells. The identification of key miRNAs, hsa-miR-27a-3p, hsa-miR-30c-5p, and hsa-miR-181a-5p targeting both aromatase and SIRT1, provides an approach with novel insights on neurology-associated diseases.
Keywords: hsa-miR-30c-5p